Implementasi Permainan Kooperatif untuk Meningkatkan Keterampilan Sosial dalam Pembelajaran Tematik - Lina Izza Mazida; Dyah Afifah Andari (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
This research aims to expose data on the improvement of students' social skills by using stimulus through cooperative games by using quizzes as a reference for students in carrying out group games. Each task is carried out in a variety and variety of groups, so that learning can be carried out interactively and creatively. Cooperative games in MIN 2 Malang City are carried out on every thematic learning, in which there are several subjects. Thematic learning process, some subjects are taught integratively, thus learners are not only focused on one learning but in one lesson can simultaneously bring social skills in thematic learning.This study is a class-action study with observational data and documentation. Research in its implementation. In cycle I, 76% of students have been active in learning and 24% have not been active in learning. Students who are classified as passive the majority are male students, judging from the unresolved tasks given, not socializing with group friends, doing tasks individually. So that the expected increase in social skills is still not visible. As a result of this study, students who were active during learning had an increase to 93% from the initial percentage of 76%, seeing an increase in the activeness of male and female students judging from the tasks that were completed well, already understood the task and ran in groups. Tell peers or other groups who don't yet understand the learning material.